2021
DOI: 10.1149/1945-7111/ac3936
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Mg–Ga Compounds as Electrode Materials for Mg-Ion Batteries via Ab Initio Simulation

Abstract: The Mg–Ga alloy-type electrode is one of the potential anode materials for Magnesium-ion batteries (MIBs). In this work, the thermodynamic, electrochemical and kinetic properties of Mg–Ga compounds, i.e. Mg2Ga5, MgGa2, MgGa, Mg2Ga and Mg5Ga2, have been systematically studied. Combining the first-principles calculations and charge-discharge experimental results, the structure evolution and voltage curves of Mg–Ga compounds are presented, where the Mg–Ga compounds show low voltages and high capacity up to 1922 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Gallium (Ga), with its low melting point (29.8 °C), readily forms alloys with varying compositions with Mg. For instance different moieties of Mg x Ga y mainly; Mg 2 Ga 5 , MgGa 2 , MgGa, Mg 2 Ga, and Mg 5 Ga 2 , have been explored with theoretical specific capacities of 307, 384, 768, 1536, and 1920 mA h g −1 , respectively. 242 Recently, Wang et al reported the development of a high performance Mg 2 Ga 5 alloy anode with an outstanding long-cycle life of 1000 cycles and a relatively high rate performance at 3C. 243 The Mg 2 Ga 5 alloy was synthesized by simply pyrolyzing Ga and Mg chips at a given stoichiometric ratio under argon atmosphere.…”
Section: Mg Chemistry In Energy Storage Materialsmentioning
confidence: 99%
“…Gallium (Ga), with its low melting point (29.8 °C), readily forms alloys with varying compositions with Mg. For instance different moieties of Mg x Ga y mainly; Mg 2 Ga 5 , MgGa 2 , MgGa, Mg 2 Ga, and Mg 5 Ga 2 , have been explored with theoretical specific capacities of 307, 384, 768, 1536, and 1920 mA h g −1 , respectively. 242 Recently, Wang et al reported the development of a high performance Mg 2 Ga 5 alloy anode with an outstanding long-cycle life of 1000 cycles and a relatively high rate performance at 3C. 243 The Mg 2 Ga 5 alloy was synthesized by simply pyrolyzing Ga and Mg chips at a given stoichiometric ratio under argon atmosphere.…”
Section: Mg Chemistry In Energy Storage Materialsmentioning
confidence: 99%
“…The theoretical capacity of MgCu 2 reaches 1688 mA h/g, which exceeds that of numerous reported Mg alloy anode materials (Mg 3 Bi 2 , Mg 3 Sb 2 , Mg 2 Sn, Mg 9 Sn 5 , etc. ). ,, The ultralow diffusion energy barrier of MgCu 2 (0.318 eV) and Mg 2 Cu (0.307 eV) implies the potential for excellent rate performance. These characteristics clearly demonstrate that MgCu 2 is an excellent anode material for MIBs.…”
Section: Introductionmentioning
confidence: 99%